2015
DOI: 10.5433/1679-0359.2015v36n2p619
|View full text |Cite
|
Sign up to set email alerts
|

Não preferência para alimentação e antibiose em cultivares de amendoim a Stegasta bosquella (Chambers) (Lepidoptera: Gelechiidae)

Abstract: ResumoEste trabalho teve como objetivos avaliar a atratividade, não preferência para alimentação e antibiose em cultivares de amendoim de hábitos de crescimento ereto e rasteiro a Stegasta bosquella (Chambers). Avaliaram-se oito cultivares, sendo quatro de hábito de crescimento ereto (IAC Tatu, IAC 22, IAC 8112 e IAC 5) e quatro de hábito rasteiro (IAC Runner 886, IAC 147, IAC 125 e IAC 503). Foram realizados testes de não preferência para alimentação com e sem chance de escolha, utilizando-separes de discos f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Campos et al (2011) also verified this type of resistance in some peanut cultivars, but with lower intensity. According to Di Bello (2015), the runner peanut cultivars IAC 147 and IAC Runner 886 have antibiosis resistance that affects the larval survival of S. bosquella.…”
Section: Discussionmentioning
confidence: 99%
“…Campos et al (2011) also verified this type of resistance in some peanut cultivars, but with lower intensity. According to Di Bello (2015), the runner peanut cultivars IAC 147 and IAC Runner 886 have antibiosis resistance that affects the larval survival of S. bosquella.…”
Section: Discussionmentioning
confidence: 99%
“…The use of resistant cultivars can be considered a viable alternative method for pest control, since it does not cause adverse effects to the agro-ecosystem, reduces the population of the pest below the level of economic damage and is compatible, in general, with other control biological and chemical tactics (lARA 1991). For peanuts, several lines of research have shown promising results; BoiçA JuNioR et al (2013) found that the IAC Caiapó cultivar showed résistance to attack by Enneothrips flavens Moulton (Thysanoptera: Thripidae), while di Bello et al (2015) concluded that IAC 147, IAC Runner 886, IAC 22 and IAC 8112, showed antibiose resistance to Stegasta bosquella (Chambers) (Lepidoptera: Gelechiidae). Despite this, studies of resistance of peanut cultivars and their interaction with other control methods are still scarce.…”
mentioning
confidence: 99%